Night side of the river : ghost stories - Winterson, Jeanette, 1959- (Grove Press, 2023)
"A captivating collection of ghost stories from "one of the most gifted writers working today" (New York Times), Night Side of the River is as ingeniously provocative as it is downright spooky. In this delightfully chilling collection, the iconic Jeanette Winterson turns her fearless gaze to the realm of ghosts, interspersing her own encounters with the supernatural alongside hair-raising fictions. Lifting the veil between the living and the dead, Winterson spirits us away to a haunted estate that ensnares a nomadic young couple in its own dark past, a staged immersive ghost tour gone awry, a West Village séance that threatens the bounds between AI and reality, and a vacation home in the metaverse where a widow visits an improved version of her deceased husband. Gloriously gothic and unnervingly contemporary, Night Side of the River examines grief, revenge, and the myriad ways in which technology can disrupt the boundary between life and death"--